Modeling for Development of Simulation Tool: Impact of TCSC on Apparent Impedance Seen by Distance Relay - Khoa, N. M.; Tung, D. D. (Engineering, Technology & Applied Science Research, 2018)
The impact of thyristor controlled series capacitor (TCSC) on distance protection relays in transmission lines is analyzed in this paper. Voltage and current data are measured and collected at the relay locations to calculate the apparent impedance seen by distance protection relays in the different operating modes of the TCSC connected to the line. Short-circuit faults which occur at different locations on the power transmission line are considered in order to locate the fault for the purpose of evaluating the impact of TCSC on the distance protection relay. Matlab/Simulink simulation software is used to model the power transmission line with two sources at the two ends. Voltage source, transmission line, TCSC, voltage and current measurement, and discrete Fourier transform (DFT) blocks are integrated into the model. Simulation results show the impact of TCSC on the distance protection relay and determine the apparent impedance and fault location in the line.